Permintaan Donasi Bisnis Waralaba Dalam Etika Islam - Husnul Khotimah; Nurul Huda (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This paper examines the phenomena that occur in society, related to requests for donations to franchise businesses. What should have been change in the form of change was given to consumers, but in reality the cashier asked for the change to be donated, therefore this article was born so that people know and understand how to donate correctly according to Islamic law. This study uses a qualitative method of phenomenology. The research results show that; first, carrying out business activities must be in accordance with Islamic law guided by the Al-Qur'an and hadith. Second, in carrying out the activities of requesting donations, the franchise business lacks the application of Islamic ethical principles, the transaction actors also underestimate it because of the small nominal. Keywords: Islamic Business Ethics, Requests for Donations, Franchise Business